Pengaruh Kepatuhan Batasan Cairan, Dukungan Keluarga terhadap Kualitas Hidup pada Pasien Hemodialisa - Nia Khusniyati M; Erni Forwaty; Wiwiek Delvira (Jurnal Keperawatan, 2023)
Compliance of fluid limits is one of the factors that can improve the quality of life in hemodialysis patients. Success in adhering to fluid limits depends on support from the family. Patient non-compliance in restricting fluids can cause major and very serious consequences. The aim of this study was to determine the effect of family support and compliance with fluid limits on the quality of life in hemodialysis patients. The method used is quantitative research with a multivariate design using linear regression test analysis with the backward LR method. The sample in this study was 95 respondents using purposive sampling. The measuring instruments used are KDQOL SF-36, IDWG, and support from the Friedman family. The research results showed that there was a significant relationship between compliance with fluid limits and quality of life (p = 0.000) and family support with quality of life (p = 0.000), but the results of the linear regression test showed that compliance with fluid limits was the strongest factor influencing quality of life by 30.3 times compared to family support and the rest is influenced by other factors. The conclusion is that there is a significant influence between compliance with fluid limits and family support on the quality of life of hemodialysis patients